2012
DOI: 10.1100/2012/580863
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Function and Handgrip Strength in Rheumatoid Arthritis Patients

Abstract: Objective. To examine the relationship of handgrip strength with forearm blood flow (BF) and vascular resistance (VR) in rheumatoid arthritis (RA) patients. Methods. Forearm BF at rest (RBF) and after upper arm occlusion (RHBF), and handgrip strength were examined in 78 individuals (RA = 42 and controls (CT) = 36). Subsequently, VR at rest (RVR) and after occlusion (RHVR) were calculated. Results. The patients' RBF (P = 0.02) and RHBF (P = 0.0001) were less, whereas RVR (P = 0.002) and RHVR (P = 0.0001) were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…In addition, using a multiple linear regression analysis, we demonstrated that only disease duration was associated with HGS in the elderly population with RA. Our finding of no significant difference in HGS for both groups is clearly inconsistent with other studies which reported that the participants with RA had significantly lower HGS than healthy controls (5,20). Firstly, it has been shown that HGS can be affected by functional ability, sleep quality, anxiety and depression, cognitive impairment, fatigue; therefore, we also evaluated the groups in terms of these factors to prevent bias and found no significant difference (3,21).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, using a multiple linear regression analysis, we demonstrated that only disease duration was associated with HGS in the elderly population with RA. Our finding of no significant difference in HGS for both groups is clearly inconsistent with other studies which reported that the participants with RA had significantly lower HGS than healthy controls (5,20). Firstly, it has been shown that HGS can be affected by functional ability, sleep quality, anxiety and depression, cognitive impairment, fatigue; therefore, we also evaluated the groups in terms of these factors to prevent bias and found no significant difference (3,21).…”
Section: Discussioncontrasting
confidence: 99%
“…The reduced occlusion blood pressure and increased occlusion vascular resistance in the patients are consistent with previous studies [ 30 33 ]. Arosio et al, for example, reported a -29% in peak blood flow (p = 0.05) in rheumatoid arthritis [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…We believe that our study provides a relevant reference for the measurement of hand strength in patients with RA, as the sample size was larger compared with the studies available in the literature [37,38,41,45,47]. In addition, we used a control group composed of individuals with sociocultural profiles similar to those of the RA patients and matched per sex, age, and BMI; therefore, both the internal and external validity are satisfactory.…”
Section: Use Of Cardiovascular Medications Has Been Associatedmentioning
confidence: 94%
“…Although the analyzed studies had excluded individuals with diabetes mellitus, chronic obstructive pulmonary disease, and testosterone and/or growth hormone deficiencies, the abovementioned value is similar to the one we found in the present study, in which patients with such conditions were not excluded. Alomari et al [41] found a 30% reduction in HS among patients with RA compared with healthy individuals recruited from the local community without ischemia, systemic arterial hypertension, angina, diabetes mellitus, anemia, dyslipidemia, kidney failure, obesity, or higher cardiovascular risk and who were nonsmokers. Even without excluding participants with any of these conditions, in our study, we found a similar difference between patients and controls.…”
Section: Use Of Cardiovascular Medications Has Been Associatedmentioning
confidence: 99%